2016
DOI: 10.15408/aiq.v8i1.2505
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Run And Long-Run Relationship In The Indonesia Islamic Stock Returns

Abstract: The Short-Run and Long-Run Relationship in Indonesia Islamic Stock Returns. This paper aims at empirically examining the short-run and long-run causal relationship between the Indonesian Islamic stock returns and selected macroeconomic variables namely inflation, money supply and exchange rate during the pre-and post-2008 global financial turmoil period from 2002 until 2007 and from 2008 until 2013 by using monthly data. The methodology used in this study is time series econometric techniques i.e. the unit roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…This finding implies that to stabilize the stock markets in the country, the policy-makers should control the stability of the interest rate, as one of the monetary instruments. This finding is in line with the studies by Majid and Yusof (2009) on the Malaysian Islamic stock markets, Majid (2016) and Pratama and Azzis (2017) on the Islamic stock market of Indonesia, and Muradoglu et al (1999) on the Turkish stock market.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding implies that to stabilize the stock markets in the country, the policy-makers should control the stability of the interest rate, as one of the monetary instruments. This finding is in line with the studies by Majid and Yusof (2009) on the Malaysian Islamic stock markets, Majid (2016) and Pratama and Azzis (2017) on the Islamic stock market of Indonesia, and Muradoglu et al (1999) on the Turkish stock market.…”
Section: Resultssupporting
confidence: 91%
“…In the context of Indonesia, both short-and long-run relationship between macroeconomic determinants and Islamic stocks using Vector Error Correction Model (VECM) (Antonio et al, 2013) and variance decompositions (Majid, 2016) techniques, found that inflation, money supply, exchange rate, and crude oil price significantly affected the Islamic stocks, showing the importance of these macroeconomic determinants to be focused on when stabilizing Islamic stock markets in the country. As for measuring the volatilities of Islamic stock markets, in his simple study using only the Time Series Plots and Histogram, Tanjung (2014) found that the Jakarta Islamic Index (JII) was abnormally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…This fact will reduce the profit of various industries due to decreased sales revenue. Majid (2016) found that the Inflation, money supply, and exchange rate affect the Islamic stock returns in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies focused on the integration of Islamic stock markets is conducted by Majid and Kassim (2010) using the Autoregressive Distributed Lag (ARDL) framework during the 1999-2006 period, and documented that the Islamic stock markets tended to become more interlinked, thus implying the decline of diversification benefits when investing in the Islamic stocks globally. Moreover, other existing empirical studies on the Islamic stock market in Indonesia only measured the performance (Tulasmi and Trihariyanto, 2016) and its determinants (Majid, 2016a(Majid, , 2016bBeik and Fatmawati, 2014;Ali, 2014. Baroroh, 2013Azwar et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, other existing empirical studies on the Islamic stock market in Indonesia only examined their determinants (Majid, 2016a(Majid, , 2016bBeik and Fatmawati, 2014;Ali, 2014;Baroroh, 2013;and Azwar et al, 2011). These studies found that money supply, inflation, interest, exchange rate, the conventional stock market, economic growth affect the Islamic stock market (Baroroh, 2013;Beik and Fatmawati, 2014;Majid, 2016b). Azwar et al (2011) found that debt ratio, profitability, and interest rate affected the Islamic stock markets.…”
Section: Introductionmentioning
confidence: 99%